Hospital readmissions following HLA‐incompatible live donor kidney transplantation: A multi‐center study. Issue 3 (23rd September 2017) - Orandi, Babak J.; Luo, Xun; King, Elizabeth A.; Garonzik‐Wang, Jacqueline M.; Bae, Sunjae; Montgomery, Robert A.; Stegall, Mark D.; Jordan, Stanley C.; Oberholzer, Jose; Dunn, Ty B.; Ratner, Lloyd E.; Kapur, Sandip; et al.
Abstract : Thirty percent of kidney transplant recipients are readmitted in the first month posttransplantation. Those with donor‐specific antibody requiring desensitization and incompatible live donor kidney transplantation (ILDKT) constitute a unique subpopulation that might be at higher readmission risk. Drawing on a 22‐center cohort, 379 ILDKTs with Medicare primary insurance were matched to compatible transplant‐matched controls and to waitlist‐only matched controls on panel reactive antibody, age, blood group, renal replacement time, prior kidney transplantation, race, gender, diabetes, and transplant date/waitlisting date. Readmission risk was determined using multilevel, mixed‐effects Poisson regression. In the first month, ILDKTs had a 1.28‐fold higher readmission risk than compatible controls (95% confidence interval [CI] 1.13‐1.46; P  < .001). Risk peaked at 6‐12 months (relative risk [RR] 1.67, 95% CI 1.49‐1.87; P  < .001), attenuating by 24‐36 months (RR 1.24, 95% CI 1.10‐1.40; P  < .001). ILDKTs had a 5.86‐fold higher readmission risk (95% CI 4.96‐6.92; P  < .001) in the first month compared to waitlist‐only controls. At 12‐24 (RR 0.85, 95% CI 0.77‐0.95; P  = .002) and 24‐36 months (RR 0.74, 95% CI 0.66‐0.84; P  < .001), ILDKTs had a lower risk than waitlist‐only controls. These findings of ILDKTs having a higher readmission risk than compatible controls, but a lower readmission risk after the first year than waitlist‐only controls should be considered in regulatory/payment schemas and planning clinical care. Abstract : In this multi‐center cohort study, the authors examine the risk of hospital readmission for live donor kidney transplant recipients requiring peritransplant desensitization compared to compatible live donor kidney transplant recipients and waitlist‐matched controls.